Life histories of Theban tombs : transdiciplinary investigations of a cluster of rock-cut tombs at Sheikh 'Abd el-Qurna - Loprieno-Gnirs, Andrea (AUC Press archaeological reports., 2021)
"In recent years, archeological research has undergone major changes. The material turn in archaeology and related disciplines prompted the adoption of sophisticated scientific, digital, and technical approaches and methods often conducted on a micro level, enhancing our understanding of depositional processes and of the creation and life of an archeological object. This volume reflects seven seasons of transdisciplinary archaeological research at a cluster of rock-cut tombs in Sheikh Abd al-Qurna, an ancient Egyptian hillside cemetery and part of the much larger Theban Necropolis. Organized in twelve main chapters, Life Histories of Theban Tombs presents current investigations in landscape archaeology (including recent excavations at a large debris hill previously covering a tomb), geo- and bioarcheology, the archaeology of tomb construction, burial practices, and domestic uses as well as various epigraphical, visual, and material studies[should there be a serial. The last two sections provide additional insight into the applied recording, surveying, and visualization methods and techniques and the database system used for data recording and organization. "